Effect of Lactobacillus plantarum Biofilms on the Adhesion of Escherichia coli to Urinary Tract Devices - Fábio M. Carvalho; Rita Teixeira-Santos; Filipe J. M. Mergulhão; Luciana C. Gomes (MDPI AG, 2021)
Novel technologies to prevent biofilm formation on urinary tract devices (UTDs) are continually being developed, with the ultimate purpose of reducing the incidence of urinary infections. Probiotics have been described as having the ability to displace adhering uropathogens and inhibit microbial adhesion to UTD materials. This work aimed to evaluate the effect of pre-established Lactobacillus plantarum biofilms on the adhesion of Escherichia coli to medical-grade silicone. The optimal growth conditions of lactobacilli biofilms on silicone were first assessed in 12-well plates. Then, biofilms of L. plantarum were placed in contact with E. coli suspensions for up to 24 h under quasi-static conditions. Biofilm monitoring was performed by determining the number of culturable cells and by confocal laser scanning microscopy (CLSM). Results showed significant reductions of 76%, 77% and 99% in E. coli culturability after exposure to L. plantarum biofilms for 3, 6 and 12 h, respectively, corroborating the CLSM analysis. The interactions between microbial cell surfaces and the silicone surface with and without L. plantarum biofilms were also characterized using contact angle measurements, where E. coli was shown to be thermodynamically less prone to adhere to L. plantarum biofilms than to silicone. Thus, this study suggests the use of probiotic cells as potential antibiofilm agents for urinary tract applications.